An Analysis of the Effects of Investment Decisions, Funding Decisions, and Dividend Policies on Firm Value - Zaldi, Shadhwina; Nabilah, Aisyah; Apribi, Cika Tri; Zainab, Siti (Universitas Mercu Buana, 2024)
The global economy is still experiencing instability in the capital market. Several factors cause capital market instability. One of the factors that affect the capital market is financial information. Financial information can affect stock prices and overall company value. This study aims to analyze the effect of investment decisions, funding decisions, and dividend policies on firm value. The method used uses quantitative methodology with an associative approach. The population of this study are public companies listed on the Bursa Efek Indonesia with Food and Beverages companies as samples. The sampling method used is purposive sampling method. Samples were collected from 8 Food and Beverages companies listed on the Bursa Efek Indonesia during 2017—2023. The data analysis technique uses the classical assumption test, multiple linear regression equation, coefficient of determination (R² test), and hypothesis testing. The results show that: (1) Investment decisions influence firm value; (2) Funding decisions have no effect on firm value; (3) Dividend policies has no effect on firm value; and (4) Investment decisions, funding decisions, and dividend policies have an influence on firm value with an influence of 40.3%.